2020
DOI: 10.1016/j.neuron.2020.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and Spatial Resolution of Cell Types in the Mammalian Habenula

Abstract: Highlights d scRNA-seq identifies transcriptional cell types in the mammalian habenula d Zebrafish and mouse habenula are transcriptionally conserved d Topographical and functional organization of transcriptionally defined cell types d Identification of transcriptional cell types in response to aversive stimulus

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
120
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 111 publications
10
120
0
Order By: Relevance
“…Both our study ( Supplementary Fig. 4 ) and previous reports showed that OxR2 has a larger population in the LHb than OxR1 ( Hashikawa et al, 2020 ; Zhang et al, 2018 ), indicating that OxR2 is more likely involved in the modulation of LHb function. However, the regulatory effect of OxR1 signaling in the LHb is worth investigating in the future.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Both our study ( Supplementary Fig. 4 ) and previous reports showed that OxR2 has a larger population in the LHb than OxR1 ( Hashikawa et al, 2020 ; Zhang et al, 2018 ), indicating that OxR2 is more likely involved in the modulation of LHb function. However, the regulatory effect of OxR1 signaling in the LHb is worth investigating in the future.…”
Section: Discussionsupporting
confidence: 76%
“…Exposure to chronic social stress significantly increases the excitability of LHb neurons ( Huang et al, 2019 ). LHb neurons encode mRNA for both OxR1 and OxR2, but with higher proportion of OxR2 ( Hashikawa et al, 2020 ). These studies suggest that orexinergic projections from the LHA to the LHb may also mediate depression-like behavior induced by social stress.…”
Section: Introductionmentioning
confidence: 99%
“…To link the molecular and physiological properties of single cells, researchers applied a combined method of whole-cell recording and single-cell RNA sequencing (scRNA-seq) to individual neurons in acute slices in early studies and named this method “patch-seq” [ 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 ]. The basic protocol of patch-seq is as follows: researchers perform whole-cell recording from individual neurons from living tissue slices or even intact animals and aspirate the cell contents through a patch pipette for subsequent RNA sequencing.…”
Section: Hybrid Methodologies With In Vivo Whole-cell Recording Tementioning
confidence: 99%
“…Wagner, et al 25 used in situ hybridization images from the Allen Brain Atlas to map transcript expression throughout the LHb and its subregions, finding ten distinct anatomical patterns of expression. Recent single cell RNAseq profiles of the habenular nuclei identified several types of distinct neurons 26,27 , although none of these appeared to be pathway-specific. However, these studies did not explicitly examine gene expression between the three major LHb outputs.…”
mentioning
confidence: 99%
“…Given the heterogeneity of the LHb transcriptome and the functional differences between its anatomically segregated output pathways, it seems plausible that gene expression in these pathways respond differentially to stress. Additionally, while both Hashikawa, et al 27 and Wallace, et al 26 studied the murine habenula, this is the first study examining the genetic profile of LHb neurons in the rat.…”
mentioning
confidence: 99%